Salivary Alkaline Phosphatase and Periodontal Disease (Mustansiria Dental Journal, 2018)
Saliva is an easily collected fluid that contains locally and systemically derivedmarkers of periodontal disease. The purpose of this study was to compare the level ofsalivary alkaline phosphatase activity in healthy subjects and patients with periodontaldisease (gingivitis and periodontitis), and to evaluate the relationship of this enzymewith different clinical parameters in all patients included in the study.The study included 65 patients referred to Department of Oral Diagnosis, Collegeof Dentistry, University of Baghdad, they were divided into three groups, 20 healthysubjects, 20 subjects with gingivitis and 25 one with periodontitis. The clinicalparameters including plaque index (PI), gingival index (GI), probing pocket depth(PPD) and clinical attachment loss (CAL) were recorded and salivary samplescollected for analysis of alkaline phosphatase (ALP) levels.A highly significant increase in mean values of clinical parameters was found inpatients with periodontal disease (gingivitis and periodontitis) compared to healthysubjects, also a highly significant increase in the mean values of alkaline phosphataseactivity was illustrated as the severity of periodontal disease increased. ALP level wasclosely related to the gingival index, probing depth and attachment loss in patientswith periodontal disease, while no relation was shown to plaque index.Salivary alkaline phosphatase could be used as a useful marker for monitoringperiodontal disease.